Experimental Study of a Hybrid Wave Energy Converter Integrated in a Harbor Breakwater - Paulo Rosa Santos (2019)
Sea ports are infrastructures with substantial energy demands and often responsible for air pollution and other environmental problems, which may be minimized by using renewable energy, namely electricity harvested from ocean waves. In this regard, a wide variety of concepts to harvest wave energy are available and some shoreline technologies are already in an advanced development phase. The SE@PORTS project aims to assess the suitability and viability of existing wave energy conversion technologies to be integrated in harbor breakwaters, in order to take advantage of their high exposure to ocean waves. This paper describes the experimental study carried out to assess the performance of a hybrid wave energy converter (WEC) integrated in the rubble-mound structure that was proposed for the extension of the North breakwater of the Port of Leixoes, Portugal. The hybrid concept combines the overtopping and the oscillating water column principles and was tested on a geometric scale of 1/50. This paper is focused on the assessment of the effects of the hybrid WEC integration on the case-study breakwater, both in terms of its stability and functionality. The 2D physical model included the reproduction of the seabed bathymetry in front of the breakwater and the generation of a wide range of irregular sea states, including extreme wave conditions. The experimental results shown that the integration of the hybrid WEC in the breakwater does not worsens the stability of its toe berm blocks and reduces the magnitude of the overtopping events. The conclusions obtained are therefore favorable to the integration of this type of devices on harbor breakwaters.